Implementasi Dan Rancang Bangun Sistem Informasi Arsip Dan Tracking Inspeksi Pada BPOM Pekanbaru - Muhammad, Muhammad; Maria, Sinta; Simatupang, Julianto; Mukhtar, Mukhtar (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2023)
At present, BPOM Pekanbaru, in the field of inspection, still uses manual methods for archiving and tracking. Therefore, employees need a long time to do archives because they are still inputted into the Microsoft Excel application. Besides that, to know the status of the submission letter, employees have to go back and forth asking and checking documents from related parties to see whether it has been followed up or not. The purpose of this research is intended for employees who have access rights to make it easier to do archives. For employee tracking activities, it is enough to check the status of the system regarding the progress of the letter and whether it has been followed up or not. The method used is a waterfall; this method is suitable for archiving and tracking problems in the inspection division because it starts from the stages of problem analysis, system design, building the system, and testing the system that has been built. The results of this study are in the form of an archive and tracking information system in the inspection division so that employees can be facilitated in archiving and monitoring documents that have been submitted.